2011
DOI: 10.1039/c0cc02204g
|View full text |Cite
|
Sign up to set email alerts
|

A solid-state trimerisation of a diene diacid affords a bicyclobutyl: reactant structure from X-ray powder data and product separation and structure determination viaco-crystallisation

Abstract: A bicyclobutyl that bears six carboxylic acid groups results from a trimerisation of a diene diacid in the solid state. Powder X-ray diffraction and a co-crystallisation are used to solve the structure of the diene and elucidate the stereochemistry of the bicyclobutyl, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…The interaction between a CCF and ladderane would enable the components to pack more efficiently relative to the pure ladderane. Whereas cocrystallizations are often successfully used to aide the elucidation of the structures biological molecules (22), the application of a cocrystal strategy to determine the relative configuration of a diastereomer had not been reported (23)(24)(25)(26)(27).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction between a CCF and ladderane would enable the components to pack more efficiently relative to the pure ladderane. Whereas cocrystallizations are often successfully used to aide the elucidation of the structures biological molecules (22), the application of a cocrystal strategy to determine the relative configuration of a diastereomer had not been reported (23)(24)(25)(26)(27).…”
Section: Resultsmentioning
confidence: 99%
“…To circumvent difficulties to obtain single crystals, we revisited principles of crystal engineering by employing a cocrystallization (Scheme 3). Cocrystallizations are often used to determine structures of biomolecules (e.g., proteins) (22), yet applications to parallel problems involving small molecules have been less explored, with absolute structure determinations of steroids (23,24) and, more recently, separations and structure determinations of natural products (25,26) and a bicyclobutyl being the only examples (27). Here, a cocrystallization of the second isomer with 3,5-dinitrobenzoic acid (3,5-DNBA) readily afforded single crystals that enabled the relative configuration of chiral 1b to be confirmed.…”
mentioning
confidence: 99%
“…Formation of trimers is excluded as explained in ESI. ‡ 4 Both isomers possess the rtct topology. Indeed in the 1 H-NMR spectrum of 4 (Fig.…”
mentioning
confidence: 99%
“…We have reported that pure dmma undergoes both a dimerisation and trimerisation in the solid state to afford a mixture of products; namely, a monocyclobutane dimer and an unusual bicyclobutyl trimer. 7 The products arise from 'out-of-phase' stacking of the diene in the solid (Scheme 1a). 8 1,3-Dienes such as dmma are familiar reactants in organic solid-state photochemistry, 9 known to undergo cycloaddi- We have recently shown that dmma self-assembles in the solid state to form 1D hydrogen-bonded polymers sustained by carboxylic acid dimers.…”
mentioning
confidence: 99%
“…8 1,3-Dienes such as dmma are familiar reactants in organic solid-state photochemistry, 9 known to undergo cycloaddi- We have recently shown that dmma self-assembles in the solid state to form 1D hydrogen-bonded polymers sustained by carboxylic acid dimers. 7 Neighbouring 1D strands packed such that the nearest-neighbour carbon-carbon double (C C) bonds assembled parallel and in close proximity. The stacking of the olefins placed the dienes in an out-of-phase geometry that, upon UV-irradiation, afforded both an anti monocyclobutane dimer and a bicyclobutyl trimer as products.…”
mentioning
confidence: 99%